2018
DOI: 10.1136/bcr-2017-222250
|View full text |Cite
|
Sign up to set email alerts
|

Massive thoracic ganglioneuroma with significant mass effect on left hemithorax

Abstract: A 42-year-old, otherwise healthy, woman presented with persistent left-sided chest pain. A chest X-ray revealed a large opacity in the left hemithorax which prompted further investigation with an MRI. MRI revealed a large left apical mass occupying approximately two-thirds of the left hemithorax. The mass was investigated further with a CT with contrast which did not reveal any vascular involvement or invasion into adjacent structures. The patient successfully underwent tumour resection via left thoracotomy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Therefore, the natural cap of tumor mass growth was assumed to be limited by the provided space before any symptom onset was noticed by the patient. The largest GN currently reported was 23 cm in diameter [6]. Thus, our case currently ranks as the largest resected ganglioneuroma.…”
Section: Systematic Literature Reviewmentioning
confidence: 71%
See 1 more Smart Citation
“…Therefore, the natural cap of tumor mass growth was assumed to be limited by the provided space before any symptom onset was noticed by the patient. The largest GN currently reported was 23 cm in diameter [6]. Thus, our case currently ranks as the largest resected ganglioneuroma.…”
Section: Systematic Literature Reviewmentioning
confidence: 71%
“…As these tumors are generally diagnosed due to compressive symptoms and consequently resected in children, there is usually a natural limit to tumor size given by the available space within the body cavity. The biggest resected GN assessable through literature research up to now showed a maximum diameter of approximately 23 cm [6] in a 42-year-old patient located solely thoracically [6]. Located most commonly in the posterior mediastinum (41.5%) or retroperitoneally (37.5%), ganglioneuromas can be found in the adrenal glands (21%), in the neck (8%), retropharyngeally, or more rarely in the sella turcica [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Guan, et al reported a case with a tumor of 21 × 15 × 18 cm in an 8-year-old child [3]. The largest tumor was reported by Lambdin, et al but it was in an adult patient (24 × 10 × 10) [20] (Table 1).…”
Section: Discussionmentioning
confidence: 97%
“…This indicates that there may be a The literature review of primary intrathoracic ganglioneuroma. [15] 1992 17/F L N/A Regular No No Osterhouse [16] 2002 25/F L 15 × 7 × 3 Regular No Yes Duffy [17] 2005 27/F R N/A N/A No No Velyvis [10] 2005 15/F R 8 × 8 × 2 Regular No Yes Maruyama [18] 2007 74/F R 6.9 × 5.8 × 1.6 Regular No No Ko [19] 2007 53/F R 9 × 4.5 × 10 Regular No No Zhang [20] 2009 3/F L 5.8 × 4.5 × 4.5 Regular No No Kitagawa [21] 2010 4/F R N/A Regular No No Guan [4] 2012 [22] 2014 [23] 2017 12/F L 12 × 12 × 12 Regular No No Jeon [24] 2017 6/M R 4 × 3.5 × 2 Regular No No Lambdin [25] 2018 42/F L 23 × 10 × 10 Regular No No Algazwi [26] 2020 18/F R N/A Regular No No Elnady [27] 2020 17/F L N/A Regular No No Brock [14] 2020 12/F R 10 × 9.1 × 9.5 Regular Yes Yes Aljuboori [28] 2021 30/NA R N/A Regular No No Tiwari [29] 2022 4/F L 3.8 × 2.5 × 2.3 Regular No No (Continued ) www.md-journal.com potential association between this destructive character of GN and patients' gender. Of course, this also requires larger sample sizes and systematic analysis for verification.…”
Section: Discussionmentioning
confidence: 99%